Testing the self-teaching hypothesis in second language reading. Issue 1 (2nd January 2019) - Chung, Sheila Cira; Chen, Xi; Commissaire, Eva; Krenca, Klaudia; Deacon, S. Hélène
ABSTRACT: The self-teaching hypothesis (Share [1995]. Phonological recoding and self-teaching: Sine qua non of reading acquisition. Cognition, 55, 151–218) proposes that readers acquire word-specific orthographic representations during independent reading. We evaluate the generalisability of this theory to second language (L2) reading. In this context, we also investigate the influence of first language (L1) orthographic features on L2 orthographic learning. Participants were 52 English L1 children in grades 4 and 6 of a French immersion programme. In a self-teaching paradigm, we examined the ability to learn pseudowords in the children's L2. Children read texts that contained French pseudowords that included orthographic patterns that are either shared between English and French (e.g., ) or unique to French (e.g., ). In our novel extension, we demonstrate that children learned the target pseudowords in the L2. Interestingly, there was no difference in learning of novel words with shared and unique orthographic patterns. We interpret these findings within a model of self-teaching as applied to L2 reading.